A cellular factor is required for transcription of vaccinia viral intermediate-stage genes. - Rosales, R (1994)
The cytoplasmic location of vaccinia virus replication and evidence that the multisubunit DNA-dependent RNA polymerase, early and late stage transcription factors, capping and methylating enzymes, and poly(A) polymerase are virus encoded raised the possibility that all of the proteins needed for viral mRNA synthesis are of viral origin. Previous studies showed that four components from infected cells, the viral RNA polymerase and capping enzyme and two factors called vaccinia virus intermediate transcription factors (VITFs) 1 and 2, can reconstitute transcription of vaccinia virus intermediate-stage genes in vitro. Here, we demonstrate that VITF-2 can be isolated from the nuclei of uninfected HeLa cells as well as from the cytoplasm of infected cells. The proteins with VITF-2 activity from uninfected and infected cells cochromatographed and cosedimented, suggesting that they are identical. VITF-2 activity was found in extracts of other uninfected human and monkey cells but not in nonpermissive Trichoplusia ni insect cells or in conditionally permissive rabbit kidney 13 cells. VITF-2 activity was present, however, in a permissive line of rabbit kidney 13 cells that had been stably transfected with the vaccinia virus K1L host range gene. We suggest that the VITF-2 level acts as a gauge of the permissive state of the cell and thereby regulates the length of the early prereplicative phase of the infection.